Development of a PCR assay to detect the potential production of nivalenol in Fusarium poae - Dinolfo, María Inés (2012)
Fusarium species can produce mycotoxins, which can contaminate cereal-based food producing adverse effects for human and animal health. In recent years, the importance of Fusarium poae has increased within the Fusarium head blight complex. Fusarium poae is known to produce trichothecenes, especially nivalenol, a potent mycotoxin able to cause a variety of toxic effects. In this study, a specific primer pair was designed based on the tri7 gene to detect potential nivalenol-producing F. poae isolates. A total of 125 F. poae, four F. cerealis, two F. culmorum, one F. langsethiae, one F. sporotrichioides and seven F. graminearum, plus F. austroamericanum, F. meridionale, F. graminearum sensu stricto and F. cortaderiae from the NRRL collection were analysed, and only F. poae isolates gave a positive result for the presence of a 296-bp partial tri7 DNA fragment. Moreover, the primer set was tested from cereal seed samples where F. poae and other Fusarium species with a negative result for the specific reaction (F. graminearum, F. oxysporum, F. chlamydosporum, F. sporotrichioides, F. equiseti and F. acuminatum) were isolated, and the expected fragment was amplified. We developed a rapid and reliable PCR assay to detect potential nivalenol-producing F. poae isolates.